PENGARUH VARIASI LATIHAN SHOOTING AFTER DRIBBLING DAN SHOOTING AFTER PASSING TERHADAP AKURASI SHOOTING PADA ATLET USIA 11-13 TAHUN SSB SOCCER PRATAMA TAHUN 2021 - Fernando H. Girsang; Amir Supriadi (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
The purpose of this study was to determine the effect of training variants using Shooting After Dribbling Exercises and Shooting After Passing Exercises on Shooting Accuracy in athletes aged 11-13 years SSB Soccer Pranata in 2021. The population of this study were 30 SSB Soccer students, the technique of taking The sample used purposive sampling as many as 10 people with predetermined criteria. The data collection technique is carrying out tests and measurements of shooting accuracy in the form of pre test and post test, namely Shooting After Dribbling and Shooting After Passing. Measurement of the test is done by shooting the target ball that has been determined 5 times and then the results are added up. The results of this study indicate that (1) Shooting after dribbing and Shooting after passing exercises provide a significant increase in shooting results for players aged 11-13 years at SSB Soccer Pratama 2021. It can be seen from the difference in the average ability of students before training. and after exercise. (2) The pretest score of the players in this study was 5.4 while the score of the posttest of the players was 13.8 with t count = 10.1 and ttable = 2.13 so that it can be said that tcount >ttable. So it can be concluded that this exercise greatly affects the shooting ability of players aged 11-13 years at SSB Soccer Pratama on their shooting abilities.